The interference of tinnitus on sound localization was related to the type of stimulus - Long, Yue; Wang, Wei; Liu, Jiao; Liu, Ke; Gong, Shusheng (Frontiers in Neuroscience, 2023)
Spatial processing is a major cognitive function of hearing. Sound source localization is an intuitive evaluation of spatial hearing. Current evidence of the effect of tinnitus on sound source localization remains limited. The present study aimed to investigate whether tinnitus affects the ability to localize sound in participants with normal hearing and whether the effect is related to the type of stimulus. Overall, 40 participants with tinnitus and another 40 control participants without tinnitus were evaluated. The sound source discrimination tasks were performed on the horizontal plane. Pure tone (PT, with single frequency) and monosyllable (MS, with spectrum information) were used as stimuli. The root-mean-square error (RMSE) score was calculated as the mean target response difference. When the stimuli were PTs, the RMSE scores of the control and tinnitus group were 11.77±2.57° and 13.97±4.18°, respectively. The control group performed significantly better than did the tinnitus group (t=2.841, p=0.006). When the stimuli were MS, the RMSE scores of the control and tinnitus groups were 7.12±2.29° and 7.90±2.33°, respectively. There was no significant difference between the two groups (t=1.501, p=0.137). Neither the effect of unilateral or bilateral tinnitus (PT: t=0.763, p=0.450; MS: t=1.760, p=0.086) nor the effect of tinnitus side (left/right, PT: t=0.389, p=0.703; MS: t=1.407, p=0.179) on sound localization ability were determined. The sound source localization ability gradually deteriorated with an increase in age (PT: r2=0.153, p<0.001; MS: r2=0.516, p=0.043). In conclusion, tinnitus interfered with the ability to localize PTs, but the ability to localize MS was not affected. Spectrum information could help patients with tinnitus improve their ability to localize sound sources. Therefore, the interference of tinnitus in localizing sound sources is related to the type of stimulus.